WAYS TO USE NON-STANDARD TASKS IN MOTHER LANGUAGE LESSONS - Raxmatullayeva Shaxodat Ziyotovna (American Journals, 2025)
The article discusses the methods of using non-standard tasks in native language lessons in primary education, the importance of these methods in developing students' thinking skills, perfecting language use, increasing creative approach and supporting independent thinking. It is analyzed whether these types of tasks teach students not only to read or write, but also to use their knowledge creatively and critically.
Keywords: Non-standard exercise, non-standard tasks, creative work, task, conceptual thinking, independent thought.